SISTEM INFORMASI INVENTORI PADA KEDAI KOPI SENGGANG BERBASIS WEB - Candra Laksono, (2022)
Technology has a very important role in the process of running a business, its application provides many benefits for the business and can even increase the effectiveness of the business process itself. Senggang Coffee Shop already utilizes technology in their business processes, but it is limited only in the sales process, there are several processes such as the inventory recording process that still uses the manual method, the use of this manual method often creates problems that can disrupt the running of the business. Therefore we need a web-based inventory system to facilitate the Senggang Coffee Shop in the inventory recording process. In making this system using the PIECES method to analyze existing problems, and using UML in the system design process. The system built is web-based and uses Laravel as a PHP framework, bootstrap as a CSS framework, while for data storage it uses MySQL, for testing the Black Box Testing method is used. The results of this study resulted in an inventory information system at the web-based Senggang Coffee Shop, so that it could help Senggang Coffee Shop in managing and reporting goods data so that the stock of goods was guaranteed.